The 3Ds (development, diplomacy, and defense) in Nigerian counterinsurgency: lessons from Uruzgan - David, James Ojochenemi (Frontiers in Political Science, 2024)
Counterinsurgency (COIN) operations require a comprehensive and coordinated approach that addresses political, economic, developmental, and security factors to achieve sustainable peace and security. Despite this acknowledgement among scholars and policymakers, not all these important aspects are often given the necessary attention. This is often the case in the war against jihadist terror groups in the West African region, including Boko Haram and others. This paper examines the much-touted 3Ds (Development, Diplomacy, and Defense) approach to COIN, discussing its applicability in the COIN efforts and post-war reconstruction of jihadist-infested Nigeria based on adaptable insights from Uruzgan province in Afghanistan. Using this conceptual framework, the study engages the interaction among these fundamental aspects of COIN in the existing literature to analyze their relevance in the region. By recognizing the interdependence of these factors, the study underscores the need for a comprehensive COIN strategy characterized by significant governance and political reforms aimed at rectifying historical social and economic disparities, while at the same time addressing the Islamist impetus of these groups. Thus, COIN is underscored as encompassing various measures employed by governments, including political, administrative, military, economic, psychological, and informational strategies, used in conjunction with one another to bring about peace, stability, and transformation. Carefully harnessed, the 3Ds approach presents a template for harmonizing the fundamental aspects of an effective comprehensive COIN. Therefore, this study highlights how the utilization of the 3Ds framework can aptly address the existing insurgencies led by Jihadist groups like Boko Haram, especially as a long-term strategy within the framework of post-conflict reconstruction. Simultaneously, it serves as a preventive measure against the emergence of similar groups in the region, given the region's underlying human insecurity.